Decreasing length of maternal hospital stay is not associated with increased readmission rates - Jane B. Ford; Charles S. Algert; Jonathan M. Morris; Christine L. Roberts (Australian and New Zealand Journal of Public Health, 2012)
Abstract Objective: To investigate changes in maternal length of postnatal stay by mode of birth and hospital type, and examine concurrent maternal readmission rates and reasons for readmission. Methods: Linked birth and hospital separation data were used to investigated mothers’ birth admissions (n=597,475) and readmissions (n=19,094) in the six weeks post‐birth in New South Wales, 2001–2007. Outcomes were postnatal length of stay (mean days) and rate of readmission per 100 deliveries. Poisson regression was used to investigate annual readmission rates and Wilcoxon‐Mann‐Whitney test was used to compare length of readmission stays. Results: The overall mean postnatal length of stay declined from 3.7 days in 2001 to 3.4 days in 2007. Private hospitals had longer stays after Caesarean and vaginal deliveries, but mean length of stay fell for both private and public hospitals, and both modes of birth. The maternal readmission rate fell from 3.4% in 2001 to 3.0% in 2007. Leading primary diagnoses at readmission following vaginal birth were postpartum haemorrhage and breast/ lactation complications and following Caesarean section were wound complications and breast/ lactation complications. Conclusions: Despite the decrease in mean length of stay for birth admissions, there was no increase, and in fact a decrease, in the rate of postnatal readmissions. Implications: Current practices in hospital length of stay and care for women giving birth do not appear to be having serious adverse health effects as measured by readmissions.